Peran Guru Akidah Akhlak Dalam Penanaman Nilai-Nilai Moderasi Beragama Pada Siswa - Aziz, Jamil Abdul; Solihin, Ahmad; Wijaya, Guntur (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2024)
Tolerant behavior towards existing comparisons, and openness in accepting diversity are moderate thoughts in Islam. But moderation is often misinterpreted in the context of religion in Indonesia. Religious moderation has important values ​​such as perspective, behavior, and attitude of always taking a position in the middle, always playing a fair role, and not being extreme in religion, religious diversity is the strongest in forming radicalism. The emergence of extreme groups that continue to spread their wings is influenced by various things such as the sensitivity of religious life, with the existence of Islamic sciences that are disseminated, namely Islamic sciences that have a nuance of moderation. Religious moderation behavior shows a tolerant attitude, respects every difference of opinion, respects diversity, and does not impose the will in the name of religious understanding by means of violence. This study uses a qualitative approach with a type of field research. While the data collected are in the form of primary and secondary data, data collection techniques are carried out by observation, interviews and documentation. From this study, the author got several conclusions, namely: The instillation of moderation values ​​in the learning of Aqidah Akhlak was carried out by the Aqidah Akhlak teacher, namely the value of tolerance instilled through learning. Meanwhile, for fair values, it is instilled by the Aqidah Akhlak teacher directly giving examples to students. This requires intensive supervision time to be able to find out the impact directly, while from the student's side, the impact of instilling these values ​​is shown through polite and courteous attitudes and respect. from instilling these values ​​is shown through polite and courteous attitudes and respect.